Dual-band wide-angle metamaterial perfect absorber based on the combination of localized surface plasmon resonance and Helmholtz resonance - Changlei Zhang; Cheng Huang; Mingbo Pu; Jiakun Song; Zeyu Zhao; Xiaoyu Wu; Xiangang Luo (Scientific Reports, 2017)
Abstract In this article, a dual-band wide-angle metamaterial perfect absorber is proposed to achieve absorption at the wavelength where laser radar operates. It is composed of gold ring array and a Helmholtz resonance cavity spaced by a Si dielectric layer. Numerical simulation results reveal that the designed absorber displays two absorption peaks at the target wavelength of 10.6 μm and 1.064 μm with the large frequency ratio and near-unity absorptivity under the normal incidence. The wide-angle absorbing property and the polarization-insensitive feature are also demonstrated. Localized surface plasmons resonance and Helmholtz resonance are introduced to analyze and interpret the absorbing mechanism. The designed perfect absorber can be developed for potential applications in infrared stealth field.